Implementing a 3D printing service in a biomedical library...116th Annual Meeting Medical Library Association, Inc. Toronto, ON, Canada May 15-20, 2015 - Walker, Verma (Journal of the Medical Library Association, 2017)
Three-dimensional (3D) printing is opening new opportunities in biomedicine by enabling creative problem solving, faster prototyping of ideas, advances in tissue engineering, and customized patient solutions. The National Institutes of Health (NIH) Library purchased a Makerbot Replicator 2 3D printer to give scientists a chance to try out this technology. To launch the service, the library offered training, conducted a survey on service model preferences, and tracked usage and class attendance. 3D printing was very popular, with new lab equipment prototypes being the most common model type. Most survey respondents indicated they would use the service again and be willing to pay for models. There was high interest in training for 3D modeling, which has a steep learning curve. 3D printers also require significant care and repairs. NIH scientists are using 3D printing to improve their research, and it is opening new avenues for problem solving in labs. Several scientists found the 3D printer so helpful they bought one for their labs. Having a printer in a central and open location like a library can help scientists, doctors, and students learn how to use this technology in their work.